The Effect of Quality of Service and Price on Customer Satisfaction at RM Mang Kabayan - Suryanto Sosrowidigdo (Enrichment : Journal of Management, 2022)
To meet the needs of people's lives, today's service companies are becoming increasingly diverse. A service business is a business that works for the happiness of the customer. Service companies such as RM Mang Kabayan are well-known examples of service businesses. This study aims to determine and assess the impact of service quality and price on customer satisfaction. Participants in this study were customers of the RM Mang Kabayan Bintaro branch. This study uses quantitative approaches such as interviews, questionnaires, and documentation. Primary data was obtained through the distribution of a short survey using the Slovin method and a sample of 150 respondents. Multiple linear regression was used in this study. The findings reveal that service quality and price affect customer satisfaction with the RM Mang Kabayan Bintaro branch services. Each element has a beneficial and significant influence on customer satisfaction with the RM Mang Kabayan Bintaro branch service.